2020
DOI: 10.1103/physrevaccelbeams.23.021302
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of high charge ion beams with achromatic divergence by petawatt laser pulses

Abstract: We present a study of laser-ion acceleration, where an increased laser spot size leads to sheath field geometries that accelerate ion beams of narrow and achromatic divergence at unprecedented charge densities, resulting from the high aspect ratio of the laser spot size to the acceleration distance. Matching the laser pulse length to the transverse laser spot size mitigated laser sweeping across the target front side and optimized the acceleration, with maximum energies deviating significantly from a linear in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 42 publications
2
25
1
Order By: Relevance
“…As it was mentioned in the introduction, the oblique incidence of a large focal diameter laser pulse at the target introduces a sweeping effect, which was identified in Ref. 36. When such a laser interacts with a foil, the effective spot on the target is defined as…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As it was mentioned in the introduction, the oblique incidence of a large focal diameter laser pulse at the target introduces a sweeping effect, which was identified in Ref. 36. When such a laser interacts with a foil, the effective spot on the target is defined as…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In Ref. 36, this effect was utilized to estimate the scale length by comparing the experimental data with the simulation results. It was found that L ¼ 0:01k matches well the experimental data.…”
Section: A Electron Temperature and Proton Accelerationmentioning
confidence: 99%
See 1 more Smart Citation
“…From a more fundamental viewpoint, recent investigations to further improve ion acceleration performance focus on the interaction parameters affecting the energy density of laser-heated fast electrons, namely their divergence, peak current and temperature. It is well known that fast electron generation is strongly modified by the size of the laser focal spot 9 , 10 , and more effectively by the scale-length of the plasma at the vacuum-target interface. Indeed, several modelling studies based on Particle-In-Cell (PIC) simulations predict a significant increase of the proton cut-off energy with optimized pre-plasma conditions.…”
Section: Introductionmentioning
confidence: 99%
“…When focused to micrometer-sized spots, the peak intensity reaches a regime where matter is easily ionized and the electrons quiver at relativistic speeds. Nonlinear laser-plasma processes can then be accessed, driving applications such as laser-plasma acceleration (LPA; where plasma electrons are accelerated to gigaelectronvolt-level energies over distances of just centimeters [6] ), LPA-based light sources [7][8][9][10] , plasma-based X-ray lasers [11] , and ion acceleration from solid targets [12] , among others.…”
Section: Introductionmentioning
confidence: 99%